2021
DOI: 10.3389/fpsyg.2020.613908
|View full text |Cite
|
Sign up to set email alerts
|

Self-Oriented Empathy and Compassion Fatigue: The Serial Mediation of Dispositional Mindfulness and Counselor’s Self-Efficacy

Abstract: This study aimed to explore the association between self-oriented empathy and compassion fatigue, and examine the potential mediating roles of dispositional mindfulness and the counselor’s self-efficacy. A total of 712 hotline psychological counselors were recruited from the Mental Health Service Platform at Central China Normal University, Ministry of Education during the outbreak of Corona Virus Disease 2019, then were asked to complete the questionnaires measuring self-oriented empathy, compassion fatigue, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…This is apparently different to being overwhelmed to the point of coping badly as implied by the nature of the IRI items. Zhang et al (2021) also found that, "Self-oriented empathy was positively associated with compassion fatigue" (p. 1). This makes absolute sense; personal distress, as measured by the IRI, not self-oriented empathy, is associated with compassion fatigue.…”
Section: Contains Items Such Asmentioning
confidence: 86%
See 2 more Smart Citations
“…This is apparently different to being overwhelmed to the point of coping badly as implied by the nature of the IRI items. Zhang et al (2021) also found that, "Self-oriented empathy was positively associated with compassion fatigue" (p. 1). This makes absolute sense; personal distress, as measured by the IRI, not self-oriented empathy, is associated with compassion fatigue.…”
Section: Contains Items Such Asmentioning
confidence: 86%
“…In summary, the use of the term "self-oriented empathy" in this paper (Zhang et al, 2021) is confusing and the paper would be enhanced if it were re-written to reflect the fact that it is personal distress that is associated with compassion fatigue.…”
Section: Contains Items Such Asmentioning
confidence: 99%
See 1 more Smart Citation
“…They need to deal with diverse and significant psychological problems of an increasing number of people each day. The heightened level of work pressure may affect their mental health and wellbeing (Zhang et al, 2021). In China, the pandemic also leads to physical and psychological consequences significantly with more than 90-thousand infections and more than 20% Chinese public suffering from mental distress by end of April 2020 (Ren et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Negative relations to physiological stress ( Lannin et al, 2019 ) and positive relations with cognitive flexibility and emotional literacy ( Asude and Zeynep, 2020 ) were also discussed. Additionally, several studies indicated positive relations of CSE with therapeutic and supervisory experience (e.g., Larson et al, 1992 ; Zhang et al, 2020 ). Nevertheless, there have been mixed results concerning counselor performance (e.g., Johnson et al, 1989 ; Larson et al, 1992 ).…”
Section: Introductionmentioning
confidence: 99%